Sieges of the barricade press and the satirical press in the 19th century in Chile - Carvajal, Carolina (2017)
This article explores the transgressor dimension of the barrice press and the satirical press in the 19th century in Chile in the context of formation of Republics.The analysis pretends to establish that both types of newspapers were a fundamental weapon in the transformation and intervention in nineteenth-century society. This is reflected in the journals of authors as Santiago Arcos, Eusebio Lillo, Francisco Bilbao y Juan Rafael Allende. The study of these types of press serves as an approach to a foundational period, in which the political, social and economic features of the American countries were configured.